Communication Pattern in Blora Community of Tilik Tradition - Dewi Ikke Nuryani (ITScience (Information Technology and Science), 2022)
Tilik is a tradition of visiting sick people that exists in Indonesian culture. This tradition is also found in Blora people. This study aims to describe the communication patterns of the Blora people in the tilik tradition. This study uses a qualitative descriptive method using an ethnographic communication approach. The data is in the form of conversations between residents of Blora in carrying out the tradition of Tilik. Data were obtained by the participatory observation method. The results of the study show that there is a communication pattern of the Blora people when visiting sick people (Tilik). The first is an introduction that contains greetings and pleasantries, after that the main points of the conversation are asking about illnesses, discussing similar illnesses, and providing solutions and messages. Then it ends with a closing containing a prayer and asks for leave. The language used in the tilik tradition follows mastery of the language and depends on the level of familiarity of the speaker and the interlocutor. If both speakers are more familiar, they will use ngoko Javanese language or rough Javanese language. If both speakers are not too familiar, they will use the fine Javanese language (kromo) with the aim of respecting each other and maintaining each other's image. Health terminology is also often inserted when visiting sick people such as hospital, MRI, hospitalized, Emergency unit, EMG, etc